In vitro antioxidant properties, free radicals scavenging activities of extracts and polyphenol composition of a non-timber forest product used as spice: Monodora myristica - Moukette, Bruno Moukette (Biol Res, 2015)
BACKGROUND: Excessive production of free radicals causes direct damage to biological molecules such as DNA, proteins, lipids, carbohydrates leading to tumor development and progression. Natural antioxidant molecules from phytochemicals of plant origin may directly inhibit either their production or limit their propagation or destroy them to protect the system. In the present study, Monodora myristica a non-timber forest product consumed in Cameroon as spice was screened for its free radical scavenging properties, antioxidant and enzymes protective activities. Its phenolic compound profile was also realized by HPLC. RESULTS: This study demonstrated that M. myristica has scavenging properties against DPPH(•), OH(•), NO(•), and ABTS(•) radicals which vary in a dose depending manner. It also showed an antioxidant potential that was comparable with that of Butylated Hydroxytoluene (BHT) and vitamin C used as standard. The aqueous ethanol extract of M. myristica barks (AEH); showed a significantly higher content in polyphenolic compounds (21.44 ± 0.24 mg caffeic acid/g dried extract) and flavonoid (5.69 ± 0.07 quercetin equivalent mg/g of dried weight) as compared to the other studied extracts. The HPLC analysis of the barks and leaves revealed the presence of several polyphenols. The acids (3,4-OH-benzoic, caffeic, gallic, O- and P- coumaric, syringic, vanillic), alcohols (tyrosol and OH-tyrosol), theobromine, quercetin, rutin, catechine and apigenin were the identified and quantified polyphenols. All the tested extracts demonstrated a high protective potential on the superoxide dismutase (SOD), catalase and peroxidase activities. CONCLUSION: Finally, the different extracts from M. myristica and specifically the aqueous ethanol extract reveal several properties such as higher free radical scavenging properties, significant antioxidant capacities and protective potential effects on liver enzymes.